Membangun Decision Support System Berbasis Financial Technology Dalam Berinvestasi Saham - Kartanto, Lucky (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2020)
At present, investment is well known in Indonesian society, investment awareness by the public has begun to increase along with the existence of several investment instruments that are widely offered by bank financial institutions, non-bank financial institutions, as well as various types of investment options on the Indonesia Stock Exchange. According to Sophar Lumbantoruan (1996), the notion of investment is equity participation in other companies. One form of investment known to the general public is shares traded on the Indonesia Stock Exchange. Investing always considers the results and risks that will be faced by Investors. Not all investors understand the theory of investing in stocks, especially in selecting shares in a portfolio in order to produce a certain rate of return with minimal risk. This study aims to find a decision support system (DSS) based on Financial Technology that will provide information related to stock recommendations that should be bought by investors. Stock Selection in this study are shares of listed companies listed on the Kompas 100 Index, the Analysis Technique used in this study is the Single Index Model. This research can produce recommendations for investors to buy shares in a portfolio that will provide certain benefits with minimal risk. Keyword- Investment, Decision Support System, Financial Technology, Single Index Model, Porfolio